Effects of multiple doses of gonadotropin-releasing hormone agonist on the luteal-phase support in assisted reproductive cycles: A clinical trial study - Maryam Eftekhar; Maryam Mirzaei; Esmat Mangoli; Yasamin Mehrolhasani (Shahid Sadoughi University of Medical Sciences, 2021)
Background: The effect of adding gonadotropin-releasing hormone (GnRH) agonist on the luteal phase support in assisted reproductive technique (ART) cycles is controversial. Objective: To determine the effects of adding multiple doses of GnRH agonist to the routine luteal phase support on ART cycle outcomes. Materials and Methods: This clinical trial study included 200 participants who underwent the antagonist protocol at the Research and Clinical Center for Infertility, Yazd, Iran, between January and March 2020. Of the 200, 168 cases who met the inclusion criteria were equally divided into two groups - the case and the control groups. Both groups received progesterone in the luteal phase, following which the case group received GnRH agonist subcutaneously (0/1 mg triptorelin) zero, three, and six days after the fresh embryo transfer, while the control group did not receive anything. Finally, chemical and clinical pregnancy rates, number of mature oocytes, fertilization rate, total dose of gonadotropin, and the estradiol level were determined. Results: The baseline characteristics were similar in both groups. No significant difference was observed between embryo transfer cycles. Clinical results showed that differences between the fertilization rate, chemical and clinical pregnancies were not significant. Conclusion: The results showed that receiving multiple doses of GnRH agonist in the luteal phase of ART cycles neither improves embryo implantation nor the pregnancy rates; therefore, further studies are required.